Characterization of quorum sensing‐controlled transcriptional regulator MarR and Rieske (2Fe–2S) cluster‐containing protein (Orf5), which are involved in resistance to environmental stresses in Pseudomonas syringae pv. tabaci 6605. (7th October 2014) - Taguchi, Fumiko; Inoue, Yuko; Suzuki, Tomoko; Inagaki, Yoshishige; Yamamoto, Mikihiro; Toyoda, Kazuhiro; Noutoshi, Yoshiteru; Shiraishi, Tomonori; Ichinose, Yuki
Summary: Pseudomonas syringae pv. tabaci 6605 ( Pta 6605) produces acyl homoserine lactones (AHLs), quorum sensing (QS) molecules that are indispensable for virulence in host tobacco infection. Genome‐wide transcriptional profiling of several QS‐defective mutants revealed that the expression of the genes encoding the MarR family transcriptional regulator (MarR) and a Rieske 2Fe–2S cluster‐containing protein (Orf5) located adjacent to psyI, a gene encoding AHL synthetase, are significantly repressed. Exogenous application of AHL recovered the expression of both marR and orf5 genes in the Δ psyI mutant, indicating that AHL positively regulates the expression of these genes. To investigate the role of these genes in the virulence of Pta 6605, Δ marR and Δ orf5 mutants were generated. Both mutants showed decreased swimming and swarming motilities, decreased survival ability under oxidative and nitrosative stresses and, consequently, reduced virulence on host tobacco plants. Transmission electron micrographs showed that the structure of the cell membranes of Δ marR and Δ orf5 mutants was severely damaged. Furthermore, not only the ratio of dead cells, but also the amount of flagella, extracellular DNA and protein released into the culture supernatant, was significantly increased in both mutants, indicating that the disruption of marR and orf5 genes might induce structural changes in the membrane and cell lysis. Because both mutants showed partly similar expression profiles, both gene products might be involved in the same regulatory cascades that are required for QS‐dependent survival under environmentally stressed conditions.